The Effectiveness of Red Spinach (Amaranthus tricolor L.) and Green Spinach (Amaranthus hybridus L.) Extracts for Bacillus thuringiensis var. kurstaki Protectant against UVB Radiation for the Control of Armyworm (Spodoptera litura Fab.) - Siti Sumarmi; Mifta Arlinda; Sukirno Sukirno (Universitas Gadjah Mada, 2020)
Spodoptera litura Fab. is an insect that damage cultivated plants in Indonesia. Efforts to control it can be done by using biological agents for example by using Bacillus thuringiensis kurstaki (Btk.). Unfortunately, the Btk. is easily degraded by UV radiation. This research aimed to study the effectiveness of red and green spinach as UVB protection for Btk. and to observe the pathogenicity of Btk. formulations against armyworm. Furthermore, the sublethal effect of Btk. against S. litura was investigated. The morphology of the endospore, protein crystal, and bacterium were observed under a contrast phase microscope. The extracts at 2% (w/v) were mixed with Btk. suspensions at 5 x 104, 5x105, and 5x106 (spores/ml), respectively. The formulations then exposed under Ultraviolet B (UVB) lights for 3, 6, and 9 hours then tested against the 3rd larval instar of armyworm. The larval mortality was observed daily and the analysis of variance was analyzed by one way anova. The sublethal effects of the treatment to the pupal and adult stages were observed when the moths emerge. The results showed that the larval mortality caused by Btk. mixed with red spinach ranged from 11.7 to 26.7%. The sublethal effects of Btk. resulted in smaller sizes of pupae and imago, darker pupae, and wings abnormality of the adult stage, compared to any control treatment. The morphological observation of the bacteria showed that extracts gave UV protection against UVB. These results suggested that red and green spinach potentially can be used as a protectant for Btk. against UVB.